2009
DOI: 10.1007/s12550-009-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin in Aspergillus fumigatus: an example that mycotoxins are potential virulence factors

Abstract: Moulds produce several different mycotoxins that may improve their chance of survival in particular environments. For example, Aspergillus fumigatus, an important human pathogen, produces several mycotoxins including gliotoxin. This secondary metabolite, a small lipid soluble dipeptide, exerts toxic effects on phagocytic cells and T-lymphocytes at low concentrations in vitro. A. fumigatus also produces high levels of gliotoxin in vivo, and this suggests that host defense mechanisms might be impaired by this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Gliotoxin is a small, hydrophobic nonribosomal dipeptide that exerts toxic effects on phagocytic cells and T‐lymphocytes at low concentrations in vitro . It is discussed as a virulence factor in invasive aspergillosis by suppressing the innate and adaptive immune response 34.…”
Section: Resultsmentioning
confidence: 99%
“…Gliotoxin is a small, hydrophobic nonribosomal dipeptide that exerts toxic effects on phagocytic cells and T‐lymphocytes at low concentrations in vitro . It is discussed as a virulence factor in invasive aspergillosis by suppressing the innate and adaptive immune response 34.…”
Section: Resultsmentioning
confidence: 99%
“…ellipticus producing gliotoxin and in much higher amounts. This finding, as well as the role that gliotoxin likely plays in virulence enhancement (Kupfahl et al ., ; Hof & Kupfahl, ; Kwon‐Chung & Sugui, ), makes it very interesting to evaluate the possible virulence characteristics of the variant ellipticus in future research. In addition, more research is needed to evaluate the importance of this variant in invasive infections.…”
Section: Discussionmentioning
confidence: 99%
“…gliotoxin). Increasing evidence supports a significant role of gliotoxin in hampering various defence mechanisms of the host, leading to virulence enhancement (Kupfahl et al ., ; Hof & Kupfahl, ; Kwon‐Chung & Sugui, ). The level of gliotoxin production by A. fumigatus isolates can vary or even be completely absent (Lewis et al ., ; Kosalec & Pepeljnjak, ; Boudra & Morgavi, ; Kupfahl et al ., ; Pereyra et al ., ; E. Van Pamel, E. Daeseleire, M. Heyndrickx, L. Herman, A. Verbeken & G. Vlaemynck, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Its most prominent member is the lipid-soluble gliotoxin which was shown to induce apoptosis, inhibit angiogenesis and prevent NF-κB activation by inhibiting the proteasome among other bioactivities ( Kroll et al, 1999 ; Pardo et al, 2006 ; Ben-Ami et al, 2009 ). High levels of gliotoxin are produced by Aspergillus fumigatus and it has been suggested that gliotoxin might be a virulence factor associated with invasive aspergillosis ( Hof and Kupfahl, 2009 ). A number of highly unusual transformations take place during gliotoxin biosynthesis including a stereospecific glutathione (GSH)- and pyridoxal phosphate (PLP)-dependent sulfurization of both C α atoms in the DKP-scaffold catalyzed by the sequential action of the glutathione S -transferase GliG, the peptidase GliJ and the thioesterase GliI [ Figure 1 , reaction (3)] ( Davis et al, 2011 ).…”
Section: Dkp Modification Enzymesmentioning
confidence: 99%